PERLINDUNGAN HUKUM TERHADAP EKSISTENSI KAIN TENUN SONGKE MANGGARAI SEBAGAI INDIKASI GEOGRAFIS - Ngompat, Yohanes Leonardus (Justitia et Pax, 2025)
Songke woven fabric is one form of geographical indication as well as a form of local wisdom that has important meaning for the lives of the Manggarai people. Although de facto, songke weaving is an inseparable part of the life of the Manggarai people. However, in reality there are still many violations of the existence of songke weaving itself and harm the rights of weaving activists and the community. Therefore, this research has examined and analyzed the existence of songke woven fabric as a geographical indication and examined and analyzed the legal protection of Manggarai songke woven fabric as a geographical indication. This research is a type of empirical legal research that uses qualitative data analysis methods. Based on the results of the research, it is known that the existence of songke woven fabric in Manggarai is still maintained and preserved by the community. This is indicated by the use of songke cloth both in traditional rites and used in more modern things. Songke woven fabric is also one example of a geographical indication that characterizes the Manggarai region. In addition, based on the results of the research, it is known that the legal protection of the songke woven fabric of Manggarai is still not optimal. This is because in general, songke woven fabric as a geographical indication has indeed been accommodated in the law. However, it is unfortunate that until now there has been no government effort to register or facilitate the community in registering songke weaving as a geographical indication right and there are no local regulations governing the protection of songke weaving. Therefore, to realize optimal legal protection, the Manggarai regional government must be actively involved in registering songke weaving as a geographical indication right.